Performance and emissions of a heavy duty diesel engine fuelled with palm oil biodiesel and premium diesel (2011)
Biodiesels are promoted as alternative fuels due their potential to reduce dependency on fossil fuels and carbon emissions.Research has been addressed in order to study the emissions of light duty vehicles. However, the particle matter and gaseous emissions emitted from heavy-duty diesel engines fueled with palm-biodiesel and premium diesel fuel have seldom been addressed. The objective of this study was to explore the performance and emission levels of a Cummins 4-stroke, 9.5 liter, 6-cylinder diesel engine with common rail fuel injection, and a cooled exhaust gas recirculation (EGR). The palm-biodiesel lowered maximum engine output by much as 10 %. The engine emissions data is compared to standards from 2004, and is determined to pass all standards for diesel fuel, but does not meet emissions standards for PM or NOx for palm-biodiesel.